Yeasts in Biotechnology - Peixoto Basso, Thalita (IntechOpen, 2019)
This book offers a broad understanding of several ways in which yeasts can be applied to the biotechnology industry. The seven chapters are grouped into three sections (apart from the "Introduction" section). The Animal Nutrition section comprises two chapters dealing with the utilization of yeast as a probiotic for animal nutrition. The Food Industry section addresses the utilization of yeast in food products. Finally, the Industrial Bioproducts section deals with the development of new yeast platforms as cell factories for biochemical production.